Mass Production of Large-Sized, Nonlayered 2D Nanosheets Their Directed Synthesis by a Rapid "Gel-Blowing" Strategy, and Applications in Li/Na Storage and Catalysis - Wang, Dong (Advanced materials (Deerfield Beach, Fla.), 2018)
© 2018 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.